Aplikasi Buku Tamu Undangan dengan Menerapkan QR Code Berbasis Web di Wedding Reception Donys Pelaminan - Yulisman, Yulisman; Juliani, Helen; Muhaimin, Abdi; Zulkifli, Akhmad (Jurnal Ilmu Komputer, 2022)
Abstract Recording invited guests in registering guests is one of the potential physical contacts that can increase the spread of the virus, especially Covid-19, whether it is at wedding receptions, aqiqah, or counseling events, where guests write attendance data in a limited guest book using a pen that each other and cause queues. Therefore, researchers conducted research by creating a web-based online guest book which is expected to help reduce physical contact between invited guests who are present when the queue is filling out the guest book and those who hold an event are also easy to mark the presence of invited invited guests. This online guestbook application is built on a web-based basis and applies qr code technology using the PHP Native programming language. This application is designed using UML, and the database is MySQL, as well as for the testing method used the blackbox testing method. The application was successful in testing and implementation, where the results were that the application could help the invited guests in filling out the guest book, no need to write names manually, only by bringing a smartphone/mobile phone to scan the qr code the invited guests were able to fill in the guest book. The application can minimize the occurrence of physical contact between invited guests which can reduce the spread of the Covid-19 virus. Keywords: Guestbook Application, QR Code, PHP Native, Invitation, Web, Wedding Reception Abstrak Pencatatan tamu undangan dalam mendata tamu merupakan salah satu potensi kontak fisik yang bisa meningkatkan penyebaran virus terutama Covid-19, baik itu pada pelaksanaan resepsi pernikahan, aqiqah, maupun acara penyuluhan, dimana para tamu menulis data kehadiran di buku tamu yang terbatas dengan menggunakan pena yang saling bergantian dan menyebabkan antrian. Maka dari itu peneliti melakukan peneltian dengan membuat buku tamu online berbasis web yang diharapkan dapat membantu mengurangi kontak fisik antara tamu undangan yang hadir ketika antrian dalam mengisi buku tamu dan yang mengadakan suatu acara juga mudah dalam menandai kehadiran tamu undangan yang diundang. Aplikasi buku tamu online ini dibangun berbasis web dan menerapkan teknologi qr code menggunakan Bahasa pemrograman PHP Native. Aplikasi ini dirancang menggunakan UML, dan basis data nya adalah MySQL, serta untuk metode pengujian yang digunakan metode blackbox testing. Aplikasi sukses dalam pengujian dan penerapannya, dimana hasilnya aplikasi dapat membantu para tamu udangan dalam mengisi buku tamu tidak perlu menulis nama secara manual, hanya dengan membawa smartphone/handphone untuk scan qr code tamu undangan sudah bisa mengisi buku tamu. Aplikasi dapat meminimalisir terjadinya kontak fisik antara para tamu undangan yang dapat mengurangi penyebaran virus Covid-19. Kata Kunci : Aplikasi Buku Tamu, QR Code, PHPNative, Undangan, Web, Wedding Reception